The Unlikeliest of Heroes : The Remarkable Evolution of Bilbo Baggins Through J.R.R.Tolkien'sThe Hobbit - .ZinebBOUABDALLAH, Miss.Nesrine GRAINE (My University, 2019)
ABSTRACT This dissertation deals with J R R Tolkien’s masterpiece The Hobbit, a fictional novel that tells the reader an adventure of a hobbit with a wizard and thirteen dwarves to restore their' realm and treasure. The present research focuses on the protagonist Bilbo Baggins, a young wealthy hobbit, whose importance changes gradually throughout the story. As a result, this study is going to explore the little hobbit adventures as the events progress in order to examine the hero’s development through his journey and to find out the reason behind his decision that stakes his position, reputation and his comfortable life in the aforementioned novel. Moreover, it seeks to analyze the psyche side of the character-growth. To achieve these goals, this study calls for two theories: the Jung's Archetypes and the Collective Unconscious, which help to identify the myths and the archetypes of Bilbo's journey and to analyze them using the archetype system. Added to that, "The Hero's Journey" archetype is used by Joseph Campbell which is detailed in The Hero with a Thousand Faces. The Freudian Psychoanalytical Theory is also used to study the function of Bilbo's psyche by focusing on the idea of the unconscious, id, ego, and superego which are the right tool to find Bilbo's transformation. This work will pave the way for future researchers to deal with the theme of the unlikeliest hero of other works specifically in fiction.
Keywords: Keywords: The Hobbit, JRR Tolkien, Character development, Heroism, Jung’s Archetypes Theory, The Freudian Psychoanalysis Theory